Soil erosion mitigation following forest wildfires - Alegre, Sergio Prats (2014)
This study aims to measure the effectiveness of four post-fire emergency techniques for reducing overland flow and soil erosion on the central-Portugal typical forest. The selection and development of these techniques was based on the review of the scientific background, but specially after checking throughout field rainfall simulation experiments which factors were the key for runoff and soil erosion on the specific case of high repellent soils. The forest residue mulch, a new treatment never tested before, was highly effective in reducing runoff and soil erosion in recently burnt eucalypt forest. The logging slash mulch had no obvious effect, but it was attributed to the small amounts of runoff and sediments that the untreated plots produced due to the extensive needle cast following a low severity fire. The hydromulch, a mixture of water, organic fibres, seeds, nutrients and a surfactant used in cutted slopes rehabilitation was also highly successful and was specially indicated for especially sensible areas. The utilization of polyacrylamides, a chemical agent with good performance in agricultural erosion, was not successful in post-fire runoff and soil erosion control, once that did not alter the most important key factor for soil erosion: the ground cover. The development of a new fibre optic turbidity sensor was a successful development on the soil erosion determination methodology, and its patent is being processed in the mean time.